The Impact of Digital Transformation on Business Models: A Bibliometric Study - Judijanto, Loso (Eastasouth Institute, 2025)
This study explores the impact of digital transformation on business models through a bibliometric analysis of research indexed in the Scopus database, utilizing VOSviewer for data visualization. The analysis identifies